2011
DOI: 10.14499/indonesianjcanchemoprev2iss1pp169-172
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of The Extract of Guava Leaves (Psidium guajava L) in The Rat (Rattus norvegicus L)

Abstract: Using of natural sources that have anti-inflammatory activity for the prevention and treatment of degenerative diseases began to be further explored. An investigation on the anti-inflammatory activity of the aqueous extract of guava leaves (Psidium guajava L.) from Sawangan, Depok on white male rats of Sprague-Dawley strain had been carried out on the carrageenan-induced paw edema method. To examine the effect of guava extract on subcutan at different doses of 125, 250 and 500 mg/kg of body weight (BW).  Indom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…In a previous study, aqueous extract of P.guajava leaves at a dose of 250 mg/ml had anti-inflammatory activity in male albino rats with arthritis induced by carrageenan. (9) From the results observed in the current investigation, it may be concluded that P. guajava leaves have a potentially in vivo antiarthritic activity, and warrants more in-depth investigations on the mechanism of action of its anti-arthritic activity. In practice, it can be developed as an alternative anti-arthritis drug.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In a previous study, aqueous extract of P.guajava leaves at a dose of 250 mg/ml had anti-inflammatory activity in male albino rats with arthritis induced by carrageenan. (9) From the results observed in the current investigation, it may be concluded that P. guajava leaves have a potentially in vivo antiarthritic activity, and warrants more in-depth investigations on the mechanism of action of its anti-arthritic activity. In practice, it can be developed as an alternative anti-arthritis drug.…”
Section: Discussionmentioning
confidence: 61%
“…The aqueous extract of guava leaves at doses of 125, 250, and 500 mg/kg had antiinflammatory activity and decreased edema in rats, with percentage inhibition of 40.81%, 55.45%, and 43.61%, respectively. (9) The Freund's adjuvant model was chosen in this study, as it develops chronic swelling in multiple joints, with influence of inflammatory cells with erosion of joint cartilage and bone destruction. Freund's complete adjuvant-induced arthritis is a well established rat model and has been widely used for many years for evaluation of the anti-inflammatory and anti-arthritic potential of various agents.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Group-A, downregulation of the arthritis index was also notable in Group-B, Group-C and Group-D. Another research group reported leaves extract decreased inhibitory activity by 40.81 %, 55.45 % and 43.61 % respectively at doses of 125, 250 and 500 mg/kg body weight in carrageenan induced rat paw edema. According to this report, leaf extract has anti-inflammatory properties by reducing edema (62).…”
Section: Anti-inflammatory Activitymentioning
confidence: 98%
“…Guava has been known for its anti-inflammatory action. [ 25 43 ] The anti-inflammatory action of guava is in its ability to inhibit prostaglandin, kinin and histamine. [ 44 ] Aa is an important periodontal pathogen and is associated with aggressive periodontitis.…”
Section: Therapeutic Applications In Treating Periodontal Diseasementioning
confidence: 99%